Effects of oil price volatility on the Kenyan stock exchange - Leiyagu, Donna Naishonva (Strathmore University, 2018)
This study seeks to examine the relationship between the international oil market performance and the performance of stocks in the Kenyan stock market. The study, therefore, employs a bivariate GARCH-BEKK (l, l) model to study this relationship and the choice of this model is driven by the fact that the model ensures positive definiteness, which makes it more effective in analysis of volatility and shock spillover. The findings of this study indicate that there exists unidirectional volatility spillover from the international oil market to the Kenyan stock market returns. The conditional variance of the Kenyan stock market returns is also seen to be affected by past volatility in the stock market.
A Research project Submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Science in Financial Economics at Strathmore University
Keywords: Stock exchange; Price volatility; Financial economics